The effectiveness of implementing credit hours co-curricular courses in Sultan Idris Education University - Rahmat, Azali; Sharil, Mohd. Izwan; Ahmad, Mohamad Ali Roshidi; Ishak, Nur Akmal; Salimin, Norkhalid (American Scientific Publishers, 2017)
This study aims to identify the role of Co-curriculum Centre in implementing the co-curricular courses for the Bachelor of Education (ISMP) students of Sultan Idris Education University. The survey’s design uses questionnaires on the effectiveness of co-curricular courses of UPSI (α = .80) on 811 respondents of eighth semester students. The findings show that all sections are given good feedbacks by the students and state that they agree that the Co-curriculum Centre provides knowledge and experience which are useful to be applied during teaching practice. The highest mean score is co-curriculum content item (m = 3.68), lecturer of the co-curricular course item (m = 3.37), support officer of co-curriculum center item (m = 3.31) and teaching aids (m = 3.15). Through ANOVA, the comparison between the four items shows significant differences of p < .05. The factor of the content of co-curricular courses offered F(3,807) = 12:59, p = .000 and co-curricular course lecturer factor F(3,807) = 4:49, p = .004. While the teaching aids factor and the officers of Co-curriculum Center did not show a significant difference. The findings show that the co-curricular courses are very beneficial to the ISMP students in guiding them to implement co-curricular activities during the teaching practice in schools. Nevertheless, the Co-curriculum Centre should always be ready to provide beneficial courses, experienced lecturer, sufficient facilities and teaching aids, and dedicated officers.